An investigation into the short-term effects of music therapy for patients with probable Alzheimer’s disease or another form of dementia. - Clute, O. (The Young Researcher)
This study aimed to address the question: to what extent are weekly music therapy sessions able to improve social interaction and heighten moods in patients suffering from different stages of Alzheimer’s disease? The study examined the progress of four participants from the O’Neill Centre in Toronto, Canada during 11 music therapy sessions over the course of six weeks. Results were measured using standardized tests prominent in the field: thee Bristol Activities of Daily Living Scale (BADLS), and Global Deterioration Scale (GDS). Although both scales showed no improvement amongst participants, positive patterns were observed by the lead researcher.